Dirty dancing : Havana nights [videorecording (DVD)] - Ferland, Guy, 1966-; Luna, Diego, 1979-; Garai, Romola, 1982-; Ward, Sela (Artisan Home Entertainment, 2004)
Set against the decedent glamour and escalating danger of revolution-era Cuba. Katey is a young American woman, who, with her family move to Cuba and discovers love, sensuality and independence. Katey persuades Javier to partner her in a prestigious national dance competition at Havana's Glittering Palace. They secretly meet to practice their dance moves at a steamy night club, where the dancing is hotter than the temperature outside. As the competetion arrives, Katey and Javier take their place as a couple on the dance floor with a sizzling style and a rhythm all thier own.